Analisis Sektor-Sektor Unggulan Perekonomian di Kabupaten Hulu Sungai Tengah - Zainab, Siti (PPJP ULM, 2018)
A country or territory will not develop if it is not supported by economic growth.Economic growth is one of the indicators to measure the success of a development.The purpose of this research is to know the superior sectors of the economy in theHulu Sungai Tengah Regency so that it can assist in the development and priority ofthe government in development. To answer the problem, then used some method ofdata analysis that is: Location Quotient Analysis (LQ) and Shift-Share Analysis. Thedata used in this research is secondary data in the value of Gross Regional DomesticProduct (GRDP) of Hulu Sungai Tengah Regency at constant prices year 2012-2016.The result of the research based on Location Quotient (LQ) analysis shows that theprimary base sector in Hulu Sungai Tengah is the sector of accommodation anddrinking (1.97%), government administration, defense and compulsory social security(1.87%), agriculture, forestry and fisheries (1.82%), education services (1.72%), realestate (1.58%), wastewater management and recycling (1.32%), information andcommunications (1.32 %), procurement of electricity and gas (1.31%), other services(1.27%), large and retail trade and auto and motorcycle repairs (1.21%),construction (1.19%), (1.19%), health services and social activities (1.11%). Theresult of Shift-Share analysis shows that there has been a shift of economic structurefrom the primary sector to the secondary sector.